2017
DOI: 10.1039/c7ra06811e
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering chemical bonding in BnHn2−(n = 2–17): flexible multicenter bonding

Abstract: It is well known that closo-borane dianions B n H n 2À are stable aromatic cages and possess n + 1 valence electron pairs, in accordance with Wade's rules. However, the electronic structures of closo-B n H n 2À cannot be explained by a Lewis structure because of their electron-deficient character, while recent theoretical and experimental studies reveal that multicenter bonding is a key part in their electronic structures. In this work, flexible multicenter bonding of B n H n 2À (n ¼ 2-17) is studied using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 95 publications
2
8
0
1
Order By: Relevance
“…To gain insight in thermodynamic hydricity of polyhedral closo-boranes, we calculated at first stage HDA MeCN of small dianionic boranes [BnHn] 2− and their lithium salts Li2[BnHn] (n = 2-4) (Figure 2), which can be formally viewed as building blocks or prototypes of polyhedral closo-boranes. Whereas [B2H2] 2− is linear, and [B3H3] 2− is planar, [B4H4] 2− has been described as having an "intermediate configuration between planar and tetragonal geometry" [133], which is actually disphenoid. In each structure, all B-Hterm bonds are equivalent (rBHterm = 1.191 Å for [B2H2] 2− ; rBHterm = 1.209 Å for [B3H3] 2− and rBHterm = 1.206 Å for [B4H4] 2− ).…”
Section: Thermodynamic Hydricity Of Polyhedral Closo-boranesmentioning
confidence: 99%
See 3 more Smart Citations
“…To gain insight in thermodynamic hydricity of polyhedral closo-boranes, we calculated at first stage HDA MeCN of small dianionic boranes [BnHn] 2− and their lithium salts Li2[BnHn] (n = 2-4) (Figure 2), which can be formally viewed as building blocks or prototypes of polyhedral closo-boranes. Whereas [B2H2] 2− is linear, and [B3H3] 2− is planar, [B4H4] 2− has been described as having an "intermediate configuration between planar and tetragonal geometry" [133], which is actually disphenoid. In each structure, all B-Hterm bonds are equivalent (rBHterm = 1.191 Å for [B2H2] 2− ; rBHterm = 1.209 Å for [B3H3] 2− and rBHterm = 1.206 Å for [B4H4] 2− ).…”
Section: Thermodynamic Hydricity Of Polyhedral Closo-boranesmentioning
confidence: 99%
“…The decrease of HDA MeCN values in this series (Scheme 7) is apparently associated with a better delocalization of electron density and with an increase in the number of possible resonance structures as the cluster size grows. In [B2H2] 2− featuring a triple B≡B bond, there are two 2c-2ē π-bonds, whereas in [B3H3] 2− and [B4H4] 2− featuring π-aromatic systems, there is one 3c-2ē and one 4c-2ē delocalized π-bond, respectively [133]. Further increase of borane cluster size results in the formation of polyhedral closo-boranes structures Li 2 [B n H n ] (n = 5-17) (Figure 3), which are formed following the Wade's rules [134,135].…”
Section: Thermodynamic Hydricity Of Polyhedral Closo-boranesmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, an improved synthesis and complete structural characterization of [B 7 H 7 ] 2– were of general interest. Although a number of theoretical studies on the structure and bonding of [B 7 H 7 ] 2– have been reported, 10 its convenient synthesis and full structural characterization were established only recently by Bernhardt in 2011. 11 In an effort to synthesize the neutral hypercloso -heptaborane analogue, Siebert reported [B 7 Cl 5 (PMe 3 ) 2 ], which was mainly characterized using 11 B NMR.…”
Section: Introductionmentioning
confidence: 99%